2012
DOI: 10.3233/jad-2012-112189
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2- and ABCG4-Mediated Efflux of Amyloid-β Peptide 1-40 at the Mouse Blood-Brain Barrier

Abstract: The accumulation of amyloid-β peptide (Aβ) in the brain is a critical hallmark of Alzheimer's disease. This high cerebral Aβ concentration may be partly caused by impaired clearance of Aβ across the blood-brain barrier (BBB). The low-density lipoprotein receptor-related protein-1 (LRP-1) and the ATP-binding cassette (ABC) protein ABCB1 (P-glycoprotein) are involved in the efflux of Aβ across the BBB. We hypothesized that other ABC proteins, such as members of the G subfamily, are also involved in the BBB clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 43 publications
7
83
1
Order By: Relevance
“…67 The pathways governing influx will be described in the next section. The cellular prion protein 68 and the multidrug transporters ABCG2 and 4 have also been shown to contribute to Ab efflux across the BBB, 69 although AD-relevant changes of these are presently unclear.…”
Section: Defects In Blood-brain Barrier Transporters That May Contribmentioning
confidence: 99%
“…67 The pathways governing influx will be described in the next section. The cellular prion protein 68 and the multidrug transporters ABCG2 and 4 have also been shown to contribute to Ab efflux across the BBB, 69 although AD-relevant changes of these are presently unclear.…”
Section: Defects In Blood-brain Barrier Transporters That May Contribmentioning
confidence: 99%
“…Shen et al (2010) used cell culture experiments to show that ABCG2 prevents cells from reactive oxygen stress via modulation of the NF-κβ pathway. Other studies found a contribution of ABCG2 to Aβ transport in vitro using different cell lines (Candela et al, 2010; Do et al, 2012; Tai et al, 2009). Do et al (2012) also proposed ABCG4 to be an Aβ40 transporter.…”
Section: Abc-transporters and Aβ – 13 Years Of Researchmentioning
confidence: 92%
“…ABCB1 deficiency increases Aβ42 levels in the hippocampus of P-gp-null transgenic mouse models of AD (AD mice) (Cirrito et al 2005). Aβ peptides are transferred by ABCG2, which is one of the major efflux pumps in the brain along with ABCB1 (Do et al 2012). On the other hand, ABCC1 knockout mice showed a significant increase in cerebral Aβ accumulation compared with either ABCB1 or ABCG2 knockout mice (Krohn et al 2011), and it was indicated that ABCB1 and ABCG2 suppress the entry of plasma Aβ into the brain (Tai et al 2009;Xiong et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…LRP2 contributes to the transport of Aβ in complex with apolipoprotein J (Zlokovic et al 1996Hammad et al 1997). ATP-binding cassette (ABC) transporters such as ABCB1 (MDR1, multidrug resistance protein 1; P-gp, P-glycoprotein), ABCC1 (MRP1 multidrug resistance-associated protein 1), ABCG2 (BCRP, breast cancer resistance protein) and ABCG4 are also supposed to be involved in the clearance of Aβ peptides from the brain (Lam et al 2001;Do et al 2012;Krohn et al 2011;reviewed by Abuznait and Kaddoumi 2012;Gosselet et al 2013). ABCB1 deficiency increases Aβ42 levels in the hippocampus of P-gp-null transgenic mouse models of AD (AD mice) (Cirrito et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation